A Research on the Undergraduate Student’s Engagement into the Pedagogy Specialization Training Using LearningApps Web Application - Dudko, Viktoriia (Computer Tools in Education, 2022)
An engagement on undergraduate students into the studying of pedagogics using the LearningApps web application is under research. Use of application’s publications in a Russian higher educational institution of pedagogics has been reviewed, including aspects and methods of research for students whose studies involve digital tools. The arguments justifying the choice of LearningApps are presented, as well as the modes of integrating the application into the pedagogical specialization. Experiment was conducted on the basis of the Vladivostok State University of Economics and Service. At the end of the semester students (n = 66) were answering a survey using a 5-point Likert scale. The results showed that the integration of LearningApps into the pedagogical specialization positively effected on student’s engagement. In the engagement profile, emotional engagement occupies the highest positions; the correlation between student’s engagement and student’s achievement has not been established. The obtained results contribute to the understanding of LearningApps as a tool for productive learning in pedagogical education sphere.
Keywords: teacher education, productive learning, student engagement, web application, educational application, LearningApps